Paradigm deleted: the materialist interpretation of the Mfecane - Peires, J.B. (Journal of southern African studies, 1993)
Continues the debate about the concept of Mfecane, the parameters of which remain very much those established by Cobbing and Omer-Cooper versus the unquestionably progressive views outlined in the 'new paradigm'.